The study of knowledge, attitudes and practices of husbands accompanying patients at obstetrics clinics of a tertiary care center about contraception - Sharma, Manisha; Sarana, Sri; Seth, Atul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Contraceptive practices are the main tool we have in controlling the ever increasing population. It also has a huge role in preventing sexually transmitted infections. The present study was undertaken to find the knowledge, attitudes and practices of husbands accompanying patient at obstetrics clinics of a tertiary care center about contraception. Methods: The study population was 100 husbands accompanying patients at obstetrics clinics of a tertiary care center. A simple questionnaire of 26 questions regarding knowledge, attitudes and practices regarding contraception was provided to the consenting husbands. The results were then analyzed. Results: Vast majority have adequate knowledge about male contraception (93%), vasectomy (85%) and sexually transmitted diseases (72%). Most of the husbands do not have adequate knowledge about female contraception (only 59%) and emergency contraception (only 27%). 70% of the husbands do not know about the free contraceptives provided by the Government of India. A staggering 74% do not participate in effective contraception. Also, 77% agreed that they would remain contended with a single child. Conclusions: This cross-sectional study clearly shows that husbands accompanying patients at obstetrics clinic of a tertiary care center have adequate knowledge about male contraception, vasectomy and sexually transmitted diseases. It is worth noting that most of the husbands do not have adequate knowledge about female contraception, emergency contraception and free contraceptives provided by the Government of India. Very few couples participate in effective contraception despite wanting to adopt a small family norm. This is a pointer towards the ineffectiveness of the family planning program of our country.